Analiza nekaterih metabesedilnih elementov v slovenskih znanstvenih člankih v dveh časovnih obdobjih - Pisanski Peterlin, Agnes (Slavistična revija, 2002)
The paper presents an analysis of he use if selected categories of metatext, previews and reviews, in 32 Slovene research articles from the fields of mathematics and archeology published 1951-1953 and 1995-1997. The research articles are analysed with a focus on the differences in the frequency with which previews and reviews occur in the texts. The results show that the selected categories of metatext are used less frequently in contemporary than in the older articles, which does not confirm the hypothesis of the growing influence of the Anglo-American model of writing.
Keywords: kontrastivna retorika; metabesedilni elementi; Slovene; slovenščina; tekstna lingvistika; znanstveni članki